THERMODYNAMIC MODELING OF REE+Y SPECIATION IN COOLING SULFATE-RICH FLUIDS - Galina P. Shironosova; Ilya R. Prokopyev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is caused by the fact that the study of speciation of lanthanide + yttrium (REE+Y) in chloride-sulfate-carbonate fluids in various weakly alkaline and weakly acidic conditions allows one to assess the effect of parameters of the ore-forming system on transportation and fractionation of rare-earth elements in oreogenesis within the carbonatite ore -magmatic systems. The main aim of the study is to estimate the contribution of the fluorine-, chloro-, carbarnate-bicarbonate, sulfate and phosphate complexes of REE+Y to transport and ore deposition by hydrothermal fluids in weakly alkaline and weakly acidic conditions at 500–100 °C and a pressure of 2000–125 bar. The methods: computational modeling of the effect of hydrothermal fluids on monazite and calcite using the HCh package (developed by Yu.V. Shvarov). To establish the equilibrium state in the program's algorithm, the method of determining the minimum Gibbs free energy of the system (the GIBBS program) in combination with the thermodynamic base UNITHERM, supplemented by experimental results for REE complexes and minerals, was used. The results. The paper introduces the distribution of REE+Y by forms in cooling chloride-sulfate-carbonate highly concentrated weakly acidic and weakly alkaline fluids. It was shown that under weakly alkaline conditions, the leading ones are the neutral and second hydroxocomplexes up to 200 °C. As the temperature decreases to 100 °С, REE+Y are found in the form of the carbonate and second fluorocomplex (Ln, Y)F2+. Under weakly acidic conditions, sulfate complexes of lanthanides prevail sharply in the entire studied range of fluid parameters. With an increase in the lanthanide number (especially for heavy REEs), the role of fluoride complexes grows with a decrease in contribution of sulfate complexes.